1997
DOI: 10.1097/00001756-199701200-00035
|View full text |Cite
|
Sign up to set email alerts
|

Functional localization of pain perception in the human brain studied by PET

Abstract: To elucidate the functional localization and somatotopic organization of pain perception in the human cerebral cortex, we studied the regional cerebral blood flow using positron emission tomography during selective painful stimulation in six normal subjects. Response to a painful stimulus was elicited using a special CO2 laser, which selectively activates nociceptive receptors, to the hand and foot. Multiple brain areas, including bilateral secondary somatosensory cortices (SII) and insula, and the frontal lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 9 publications
6
50
1
4
Order By: Relevance
“…Alternatively, it is possible that some motor activation, for example facial muscle tensions during pain may have contributed to this activation. However, we do not see this as a full explanation since the described motor activation from these muscle groups have been observed more anteriorly (at the same axial level) during pain (Casey et al, 1996;Svensson et al, 1997;Xu et al, 1997;Peyron et al, 1998). In addition, results from a fMRI study, have indicated several activations in the somatosensory association areas (S2), ranging from 28 to 228 in the y-axis and from the inner surface of the parietal operculum to the lateral surface of postcentral gurus (BA40/43) during non-painful somatosensory stimulation of the ®ngers (Gelnar et al, 1998).…”
Section: General ®Ndingsmentioning
confidence: 86%
See 1 more Smart Citation
“…Alternatively, it is possible that some motor activation, for example facial muscle tensions during pain may have contributed to this activation. However, we do not see this as a full explanation since the described motor activation from these muscle groups have been observed more anteriorly (at the same axial level) during pain (Casey et al, 1996;Svensson et al, 1997;Xu et al, 1997;Peyron et al, 1998). In addition, results from a fMRI study, have indicated several activations in the somatosensory association areas (S2), ranging from 28 to 228 in the y-axis and from the inner surface of the parietal operculum to the lateral surface of postcentral gurus (BA40/43) during non-painful somatosensory stimulation of the ®ngers (Gelnar et al, 1998).…”
Section: General ®Ndingsmentioning
confidence: 86%
“…The prede®ned matrix was chosen based on previous functional neuroimaging studies of experimental pain (Jones et al, 1991;Talbot et al, 1991;Casey et al, 1994Casey et al, , 1996Hsieh et al, 1995a;Coghill et al, 1994;Craig et al, 1996;Vogt et al, 1996;Adler et al, 1997;Andersson et al, 1997;Derbyshire et al, 1997;Gyulai et al, 1997;Rainville et al, 1997;Xu et al, 1997;Iadarola et al, 1998). However, activations in areas of BA43 and inferior parts of BA40 (BA40i) are referred to as activations in somatosensory association areas rather than secondary sensory cortex (S2) although they probably include the human homologue of S2 (see Section 4).…”
Section: Data-analysis and Statisticsmentioning
confidence: 99%
“…The insular cortex is among the brain areas that are most frequently reported as activated in response to noxious stimulation. 16,17,19,[21][22][23] More intriguing is the lack of activation in other brain areas, in particular the thalamic nuclei and the ACC. This is in contrast to other reports of functional neuroanatomy of the central processing of noxious stimuli.…”
Section: Main Effects Of Noxious Stimulationmentioning
confidence: 99%
“…Our knowledge of the involvement of the cerebral cortex in pain perception mainly derives from experimental work in animals showing that some cortical neurons Case Report 705 Fp2-F8 F8-T4 T4-T6 T6-O2 Fp1-F7 F7-T3 T3-T5 T5- respond to nociceptive stimuli (see Kenshalo and Willis 1991 for review). PET studies (Coghill et al 1994, Xu et al 1997, CO 2 laser-evoked potentials (Valeriani et al 1996), and magnetically recorded evoked potentials (Hari et al 1983) in humans have provided evidence in favour of this hypothesis. The cortical areas most likely to be involved are the primary (SI) and the secondary somatosensory area (SII), the insula, and the anterior cingulate gyrus.…”
Section: Discussionmentioning
confidence: 99%